A REVIEW OF SOME ASPECTS OF THE CORRELATION BETWEEN PEDAGOGY AND POLITICS (Annual of the Faculty of Philosophy in Skopje, 2020)
Education and upbringing, as a subject of the pedagogy in the wider meaning ofthe term, have always been of special social and state interest. The state, with its instrumentsof government, has strived to carry out its politics in the field of educationand upbringing. The word politics is associated with the terms state, state affairs, affairsof a state’s interest. This interest is very explicitly expressed in the function andthe structure of the school and the school system, especially for satisfying the fundamentalneeds of every state.In this paper some interpretations of the terms politics of education and educationpolicy are given, pointing out the differences in their treatment and meaning. Ithas been stressed that pedagogy has an autonomous position regarding the state’s educational-upbringing policy and the political factors, exponents of this policy. It hascritical attitude towards the politics and the political conception of the goals, and is alsoautonomous from the educational-upbringing practice, having a critical attitude towardsit too, since any educational-upbringing practice cannot be a source of pedagogicalcognition and raise to the level of theory which, from that position, is going to advancethe pedagogical practice. In this respect the issue of the correlation between politicsand pedagogy is reviewed by their structure: policy (educational-upbringing policy),pedagogy (science, theory), educational-upbringing practice (pedagogical practice).In these processes and correlations there must be a permanent questioning andvalorisation of the educational-upbringing policy, especially of its goals and educationalstrategy and practice, as well as of the postulates, models and instruments thepedagogy as a science offers. The realization of the goals in the development of educational-upbringing systems must be compatible with the directions of the development ofeducation at global level, but nevertheless, the success depends on the social, cultural,economic and educational context of the particular state.
Keywords: PEDAGOGY; POLITICS; EDUCATION POLICY; DEVELOPMENT; CHANGES; EDUCATIONAL–UPBRINGING SYSTEM